IN MEMORIAM: Na vest o smrti Ulricha Engela / Notice of a Death - Đorđević, Miloje (Journal of the Faculty of Philosophy in Sarajevo / Radovi Filozofskog fakulteta u Sarajevu, ISSN 2303-6990 on-line, 2020)
In Memoriam.